Antimicrobial Susceptibility Patterns of Salmonella Typhi and Salmonella Paratyphi in Tertiary Care Hospitals - Muhammad Waqas Shah, Izhar Ali, Ronaq Zaman, Fakhrud-Din, Tahir Hayat, Ikram Ullah Khan, Sami Ullah, (Pakistan Journal of Medical & Health Sciences, 2024)
Background: Salmonella typhi and Salmonella paratyphi are significant causes of enteric fever, posing substantial public health challenges globally. Monitoring their antimicrobial susceptibility patterns is crucial for guiding treatment strategies and combating antimicrobial resistance, particularly in tertiary care hospitals where severe cases are managed. Aim: To determine the antibiogram profile of Salmonella typhi and Salmonella paratyphi isolated from blood cultures of paediatrics patients presenting in Lady Reading Hospital Peshawar. Methodology: The study examined the prevalence, clinical characteristics, and antibiotic susceptibility patterns of Salmonella typhi and Salmonella paratyphi infections among 530 participants aged 13 to 18 years presenting in Lady Reading Hospital Peshawar. Over the course of two years using a prospective observational cohort design. Recruitment, clinical evaluations, and laboratory validation using accepted methods were all part of the data gathering process. Testing for antibiotic susceptibility was done, and statistical analysis was done using SPSS version 28. Both informed consent and ethical approval were obtained. Results: The research included 530 instances of enteric fever, of which 318 cases (or 60%) were due to Salmonella typhi and 212 cases (or 40%) to Salmonella Paratyphi. There were 40.25% female cases and 59.75% male cases among them. The age group of 15–16 years old accounted for the largest percentage of cases (38.68%), followed by 13–14 years old (33.02%) and 17–18 years old (28.30%). Different patterns emerged from antimicrobial susceptibility tests; drugs such as ampicillin (66.04%), azithromycin (74.26%), cefixime (87.47%), ceftriaxone (92.77%), chloramphenicol (91.51%), ciprofloxacin (92.40%), and co-trimoxazole (55.03%) showed substantial susceptibility rates. Compared to Salmonella typhi, Salmonella paratyphi showed notably greater sensitivity rates for azithromycin (94.47%) and ceftriaxone (95.45%). Practical implication: This research provided the community with important advantages and practical consequences. The study helps healthcare professionals choose efficient treatment plans by identifying the antibiotic susceptibility patterns of Salmonella typhi and Salmonella paratyphi, particularly in tertiary care facilities. Conclusion: This study highlights the importance of continuous surveillance and species-specific treatment strategies to combat antimicrobial resistance and improve patient outcomes in enteric fever, particularly in tertiary care settings. Keywords:Antimicrobial susceptibility, Salmonella typhi, Salmonella Paratyphi, Tertiary care hospitals